Educação em tempo integral e programa mais educação: aproximações e distanciamentos das regiões brasileiras em relação à meta prevista no projeto de lei do novo Plano Nacional de Educação (PNE) - Parente, Cláudia da Mota Darós [UNESP] (Editora UNIVALI, 2014)
This work presents a framework for full-time education in Brazil, analyzing the levels of proximity and distance of the Brazilian regions in relation to achieving target paragraph 06 of the bill of the new National Education Plan, which establishes the offer of full-time education in at least fifty percent of public schools, and at least twenty-five percent of students in basic education. It aims to determine the contribution of the “Mais Educação” (More Education) Program of the federal government in fulfilling this goal.

Este artigo apresenta um quadro da educação em tempo integral no Brasil, analisando a aproximação e/ou distanciamento das regiões brasileiras em relação ao cumprimento da meta nº 06 do projeto de lei do novo Plano Nacional de Educação, relativa à oferta da educação em tempo integral em, no mínimo, cinquenta por cento dos estabelecimentos públicos, atendendo, pelo menos, vinte e cinco por cento dos alunos da educação básica. Pretende-se verificar a contribuição do Programa Mais Educação do governo federal no cumprimento desta meta.

Este artículo presenta un cuadro de la educación de tiempo completo en Brasil, analizando la aproximación y/o distanciamiento de las regiones brasileñas en relación al cumplimiento de la meta nº 6 del proyecto de ley del nuevo Plan Nacional de Educación, relativa a la oferta de la educación de tiempo completo en por lo menos el cincuenta por ciento de los establecimientos públicos, atendiendo al menos al veinticinco por ciento de los alumnos de la educación básica. Se pretende verificar la contribución del Programa Más Educación del gobierno federal en el cumplimiento de esta meta.
La educación de tiempo completo y el programa más educación: aproximaciones y distanciamientos de las regiones brasileñas em relación a la meta prevista em el proyecto de ley de lo nuevo plan nacional de educación (PNE)
Full-time education and the program “mais educação” (more education): levels of proximity and distance of brazilian regions in relation to the goals and aims set by the legal framework in the new national education plan (PNE)